Developing and establishing the psychometric properties of the Strathclyde Citizenship Measure: A new measure for health and social care practice and research. (28th March 2022) - Cogan, Nicola; MacIntyre, Gillian; Stewart, Ailsa; Harrison‐Millan, Hilary; Black, Karen; Quinn, Neil; Rowe, Michael; O'Connell, Maria
Abstract: There has been increasing interest and research attention towards citizenship‐based practices and care within health and social care settings. A framework for implementing citizenship‐based interventions has helped support the participation in society of persons who have experienced major life disruptions. Yet, having ways to measure the impact of citizenship 'in action' within specific socio‐cultural contexts has proved challenging. We report on the development of the Strathclyde Citizenship Measure (SCM) which seeks to establish a psychometrically sound measure of citizenship that is relevant to the Scottish context. We outline the three phases of developing the SCM: (1) item generation, (2) item reduction and piloting, and (3) measure validation. Having generated items for the SCM using concept mapping techniques, we piloted it with 407 participants who completed an online survey of a 60‐item version of the SCM. The aims were to assess the validity of the items and reduce the number of items using principal components analysis for the final measure. This resulted in a 39 item SCM. We then sought to establish the psychometric properties of this shorter version of the SCM through testing its reliability, convergent, concurrent and discriminant validity. The 39 item SCM was administered online to 280 Scottish residents along with additional measures including the Warwick‐Edinburgh Mental Well‐being Scale (WEMWBS), the Depression, Anxiety and Stress Scale (DASS21), the Sense of Belonging Instrument (SOBI‐A); the Big Five Personality Inventory (Shortened Version; BFI‐10) and the Personal Social Capital Scale (PSCS‐16). The factor structure and dimensionality of the SCM was examined using exploratory factor analysis and it was found to be reliable and valid. This paper explores the potential for the application of the SCM across health and social care settings and identifies future work to develop citizenship tools to facilitate dialogues about citizenship across health and social care practice settings.